TiO2 / se composite buffer layer film and application thereof
Patent Information
- Application Number
- CN202610906418.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-23
- Publication Date
- 2026-10-09
AI Technical Summary
现有研究表明,若直接在TiO2、SnO2等其它电子传输层上沉积Sb2(S,Se)3,由于晶格失配和表面能差异,吸收层难以在衬底上实现有效形核,导致薄膜无法连续覆盖基底,甚至完全无法沉积
[0011]本发明的有益效果是:1.采用TiO2环保材料,通过在TiO2表面热蒸发沉积超薄Se种子层,将衬底表面的化学组成由TiO2转变为与Sb2(S,Se)3同源的Se种子层,从而降低异质形核的界面自由能和晶格失配度,为水热沉积过程中Sb2(S,Se)3晶体的形核提供有效位点,诱导实现吸收层连续、致密生长。2.采用阶梯退火工艺,先在较低温度下使硒种子层缓慢软化扩散,再升温进行高温合金化,避免传统一步高温退火导致的Se层熔融流动和薄膜脱落。3.超薄Se种子层通过热蒸发实现,水热沉积设备简单,阶梯退火仅通过程序控温即可完成,无需复杂设备,易于工业化生产。
Smart Images

Figure CN122892384A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of new energy materials and devices technology, specifically relating to a TiO2 / Se composite buffer layer film and its application. Background Technology
[0002] Antimony selenide (Sb2(S,Se)3) has attracted widespread attention as a novel photovoltaic absorber material due to its rich elemental composition, tunable band gap, and excellent photoelectric properties. Currently, the main methods for preparing Sb2(S,Se)3 thin films include near-space sublimation, vapor transport deposition, and hydrothermal deposition. In existing technologies, Sb2(S,Se)3 thin-film solar cells using cadmium sulfide (CdS) as the electron transport layer typically have the following structure: glass / FTO / CdS / Sb2(S,Se)3 / Spiro-OMeTAD / metal electrode. In this structure, the CdS layer has a dual function: (1) as an n-type electron transport layer, forming a pn junction with Sb2(S,Se)3; (2) as a "seed layer," whose surface properties are conducive to the nucleation and growth of Sb2(S,Se)3 crystals, which is key to achieving a high-quality absorber layer thin film. However, cadmium (Cd) in CdS is highly toxic, posing a potential threat to the environment and human health during production and use, thus limiting the commercial development of this technology. CdS has a narrow bandgap (approximately 2.4 eV), absorbing some short-wavelength sunlight and generating parasitic absorption, resulting in fewer photons reaching the absorption layer and limiting the short-circuit current density of the device. Therefore, there is an urgent need to develop suitable environmentally friendly electron transport layers. Existing research shows that if Sb2(S,Se)3 is directly deposited on other electron transport layers such as TiO2 and SnO2, due to lattice mismatch and surface energy differences, the absorption layer is difficult to effectively nucleate on the substrate, resulting in the film not continuously covering the substrate, or even failing to deposit at all. Summary of the Invention
[0003] The purpose of this invention is to provide a TiO2 / Se composite buffer layer thin film and its application. By thermally evaporating and depositing an ultrathin Se seed layer on the TiO2 surface, the chemical composition of the substrate surface is changed from TiO2 to a Se seed layer homologous to Sb2(S,Se)3, thereby reducing the interfacial free energy and lattice mismatch of heterogeneous nucleation and providing effective sites for the nucleation of Sb2(S,Se)3 crystals during hydrothermal deposition.
[0004] The present invention adopts the following technical solution: a TiO2 / Se composite buffer layer thin film, comprising a TiO2 electron transport layer coated on the surface of a substrate, and an ultrathin Se seed layer deposited on the surface of the TiO2 electron transport layer.
[0005] This invention also discloses a method for preparing a TiO2 / Se composite buffer layer film, characterized by comprising the following steps: Step 1: Coat an electron transport layer on the substrate surface. The electron transport layer is TiO2. Step 2: Deposit an ultrathin Se seed layer on the surface of the electron transport layer to form a TiO2 / Se composite buffer layer film; TiO 2 / Se composite buffer layer film is used to prepare Sb2(S,Se)3 absorber film by hydrothermal deposition.
[0006] Furthermore, the thickness of this ultrathin Se seed layer is 3-7 nm.
[0007] Furthermore, this ultrathin Se seed layer was deposited using a thermal evaporation method, with a vacuum degree of less than 4 × 10⁻⁴ during deposition. 4 Pa.
[0008] This invention also discloses a method for preparing a deposition sample for solar cells. The TiO2 / Se composite buffer layer film obtained by the above-described method further includes the following in step two: Step 3: Prepare a Sb2(S,Se)3 absorber film on the TiO2 / Se composite buffer film by hydrothermal deposition to obtain the deposited sample.
[0009] Further, the deposited sample in step three is subjected to step annealing: first, the sample is placed in nitrogen or inert gas and kept at 80-120℃ for 5-10 min, then the temperature is increased to 200℃ and 300℃ at a rate of 10℃ / min, and kept at each temperature for 5-10 min. Finally, the temperature is increased to 400℃ for annealing for 10 min, and after natural cooling, the Sb2(S,Se)3 absorption layer is obtained.
[0010] The present invention also discloses the application of the TiO2 / Se composite buffer layer film prepared by the above-mentioned method for preparing a TiO2 / Se composite buffer layer film, or the deposited sample prepared by the above-mentioned method for preparing a deposited sample for preparing a solar cell, in the preparation of a solar cell.
[0011] The beneficial effects of this invention are: 1. By using environmentally friendly TiO2 material, an ultrathin Se seed layer is deposited on the TiO2 surface through thermal evaporation, transforming the chemical composition of the substrate surface from TiO2 to a Se seed layer homologous to Sb2(S,Se)3. This reduces the interfacial free energy and lattice mismatch of heterogeneous nucleation, providing effective nucleation sites for Sb2(S,Se)3 crystals during hydrothermal deposition, and inducing continuous and dense growth of the absorption layer. 2. A stepped annealing process is adopted, first slowly softening and diffusing the selenium seed layer at a lower temperature, and then heating up for high-temperature alloying, avoiding the Se layer melting and flow and film detachment caused by traditional one-step high-temperature annealing. 3. The ultrathin Se seed layer is achieved through thermal evaporation, the hydrothermal deposition equipment is simple, and the stepped annealing can be completed simply by programmed temperature control, requiring no complex equipment and facilitating industrial production. Attached Figure Description
[0012] Figure 1 JV curves for devices fabricated based on different Se seed layer thicknesses on TiO2; Figure 2 The JV curves are based on the optimal Se seed layer thickness on TiO2 and the device fabricated on CdS substrate; Figure 3 The EQE curves are based on the optimal Se seed layer thickness on TiO2 and the device fabricated on CdS substrate. Detailed Implementation
[0013] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments.
[0014] The present invention discloses a TiO2 / Se composite buffer layer thin film, comprising a TiO2 electron transport layer coated on the surface of a substrate, and an ultrathin Se seed layer deposited on the surface of the TiO2 electron transport layer.
[0015] The method for preparing the TiO2 / Se composite buffer layer film described above is characterized by comprising the following steps: Step 1: Coat an electron transport layer on the substrate surface. The electron transport layer is TiO2. Step 2: Deposit an ultrathin Se seed layer on the surface of the electron transport layer to form a TiO2 / Se composite buffer layer film; the thickness of the ultrathin Se seed layer is 3-7 nm. The ultrathin Se seed layer is deposited by thermal evaporation, and the vacuum degree is less than 4×10-4 Pa during the deposition of the ultrathin Se seed layer.
[0016] TiO 2 / Se composite buffer layer film is used to prepare Sb2(S,Se)3 absorber film by hydrothermal deposition.
[0017] This invention also discloses a method for preparing a deposition sample for solar cells. The TiO2 / Se composite buffer layer film obtained by the above-described method further includes the following in step two: Step 3: Prepare a Sb2(S,Se)3 absorber film on the TiO2 / Se composite buffer film by hydrothermal deposition to obtain the deposited sample.
[0018] The deposited sample in step three was subjected to step annealing: First, the sample was placed in nitrogen or inert gas and held at 80-120℃ for 5-10 min. Then, the temperature was increased to 200℃ and 300℃ at a rate of 10℃ / min, and held at each temperature for 5-10 min. Finally, the temperature was increased to 400℃ for annealing for 10 min to improve the crystallinity of the film. After natural cooling, an Sb2(S,Se)3 absorption layer with a thickness of about 300 nm was obtained.
[0019] The present invention also discloses the application of the TiO2 / Se composite buffer layer film prepared by the above-mentioned method for preparing a TiO2 / Se composite buffer layer film, or the deposited sample prepared by the above-mentioned method for preparing a deposited sample for preparing a solar cell, in the preparation of a solar cell.
[0020] In step three, the process parameters for the precursor of the hydrothermal deposition of the Sb2(S,Se)3 absorber layer film are as follows: potassium antimony tartrate (C8H4K2O) 12 Sb2·0.5H2O), sodium thiosulfate (Na2S2O3·5H2O), and selenourea (CH4N2Se) were dissolved in ultrapure water in a certain proportion and order. After complete dissolution, the solution was transferred to a reaction vessel. The substrate was placed in the reaction vessel with its surface facing down at approximately 75° to the bottom of the reaction vessel. The reaction was then carried out at 125-135°C for 2 hours to obtain the deposited sample.
[0021] The present invention also discloses the application of the TiO2 / Se composite buffer layer film prepared by the above-mentioned method for preparing a TiO2 / Se composite buffer layer film, or the deposited sample prepared by the above-mentioned method for preparing a deposited sample for preparing a solar cell, in the preparation of a solar cell.
[0022] The solar cell structure is as follows: glass / transparent conductive layer FTO / electron transport layer / Sb2(S,Se)3 absorber thin film / hole transport layer / metal electrode. Because the Se seed layer is very thin and Se has a melting point of only about 250℃, during subsequent stepped annealing to 400℃, the Se seed layer diffuses into the Sb2(S,Se)3 and fuses with the absorber layer through alloying.
[0023] The hole transport layer is Spiro-OMeTAD; the metal electrode is either gold or silver, with a thickness of 80-100 nm. The electron transport layer has a thickness of 50-70 nm, and the Sb2(S,Se)3 absorber layer has a thickness of 800-1200 nm.
[0024] To further illustrate the TiO2 / Se composite buffer layer film and its preparation method in this invention, the following specific embodiments are provided. Example 1 The present invention discloses a method for preparing a TiO2 / Se composite buffer layer film, comprising the following steps: Step 1: Cleaning the FTO conductive glass: Place the FTO glass on a cleaning rack and sequentially clean it with semiconductor cleaning solution, ultrapure water, and ultrasonic cleaning for 20 minutes each time. Then, place it in an oven to dry for later use. Before each use, treat the FTO conductive glass substrate with ultraviolet-ozone for 20 minutes to improve surface wettability.
[0025] Preparation of TiO2 electron transport layer: A TiO2 electron transport layer was deposited on a cleaned FTO glass substrate using a spin-coating method. Specifically, a TiO2 precursor was prepared by thoroughly stirring tetrabutyl titanate, diethanolamine, anhydrous ethanol, and ultrapure water. The TiO2 precursor solution was then spin-coated onto the FTO substrate at 3000 rpm, followed by annealing at 450°C for 30 min in air to obtain a TiO2 film with a thickness of approximately 50 nm.
[0026] Step 2, Se seed layer deposition: The FTO substrate coated with the TiO2 electron transport layer is placed in a thermal evaporation coating machine, and the vacuum level is evacuated to less than 5 × 10⁻⁶. -4 Pa, using high-purity selenium particles as the evaporation source, deposited a Se seed layer with a thickness of about 3-7 nm on the surface of the TiO2 electron transport layer by controlling the evaporation current and time.
[0027] Step 3: Hydrothermal deposition of Sb2(S,Se)3 thin film: Potassium antimony tartrate (C8H4K2O) 12 Sb2·0.5H2O), sodium thiosulfate (Na2S2O3·5H2O), and selenourea (CH4N2Se) were dissolved in deionized water at a molar ratio of 4.5:18:1. After stirring evenly, the solution was transferred to a reaction vessel. The substrate with the Se seed layer deposited was placed in the reaction vessel at a 75° angle with the front side facing down. The reaction was carried out at 135°C for 2 hours. After that, the substrate was taken out, rinsed with deionized water, and dried with nitrogen to obtain the deposited sample.
[0028] Step annealing: The deposited sample was placed on a hot stage under nitrogen protection. It was first held at 80-120℃ for 10 min, and then heated to 200℃ and 300℃ at a heating rate of 10℃ / min. Each temperature was held for 5 min. Finally, it was heated to 400℃ for annealing for 10 min to improve the crystallinity of the film. After natural cooling, an Sb2(S,Se)3 absorber layer with a thickness of about 300 nm was obtained.
[0029] Hole transport layer preparation: 0.036 g of Spiro-OMeTAD powder was weighed and added to a glass bottle, followed by the sequential addition of 1 mL of chlorobenzene, 14.5 μL of 4-tert-butylpyridine, and 9.5 μL of lithium salt (the lithium salt was obtained by dissolving lithium bis(trifluoromethanesulfonyl)imide in acetonitrile, with a concentration of 520 mg / mL). After stirring at room temperature under a nitrogen atmosphere for 5 h, a Spiro-OMeTAD precursor solution was obtained. The Spiro-OMeTAD solution was then spin-coated onto a Sb₂(S,Se)₃ absorber layer at 3000 rpm for 30 s to obtain a hole transport layer with a thickness of approximately 80 nm.
[0030] Back electrode fabrication: A gold electrode with a thickness of 80 nm was deposited on the hole transport layer by thermal evaporation to obtain a complete solar cell device.
[0031] In this embodiment, different Se seed layer thicknesses were selected, and the JV curves of the devices fabricated on devices with different Se seed layer thicknesses were shown, as follows. Figure 1 As shown, the optimized Se seed layer thickness is 5 nm. When the Se seed layer thickness is 3 nm, the resulting seed layer is too thin, making it difficult to form a uniform coverage. This leads to a slow heterogeneous nucleation rate in the absorber layer, a decrease in film coverage and crystal quality, and poor device performance. When the Se seed layer thickness is 7 nm, the resulting seed layer is too thick. Due to the low melting point of Se, it is prone to melting and agglomeration during annealing, which in turn damages the uniformity and adhesion of the film, resulting in a decrease in fill factor and short-circuit current density.
[0032] The performance of the solar cell device with a Se seed layer thickness of 5 nm prepared in this embodiment was tested under standard AM 1.5G illumination (100 mW / cm²). 2 Under the given conditions, a standard xenon solar simulator (LSS-55) was used as the light source, and calibration was performed using a standard silicon cell. The JV curve of the device was recorded using a power meter. The open-circuit voltage of the device after optimizing the Se seed layer thickness was measured to be 0.613 V, and the short-circuit current density was 24.39 mA / cm². 2 The fill factor is 53.83% and the photoelectric conversion efficiency is 8.05%.
[0033] Example 2 The difference between this embodiment and Embodiment 1 is that no Se seed layer is deposited; instead, the absorber layer film is directly deposited hydrothermally on the FTO substrate with the electron transport layer TiO2. Without the Se seed layer, a continuous Sb2(S,Se)3 film cannot be formed on the TiO2 surface after hydrothermal deposition, and the absorber layer is distributed in an island-like pattern, making it impossible to fabricate a complete solar cell device.
[0034] Example 3 The difference between this embodiment and Embodiment 1 is that, instead of a stepped annealing process, a traditional one-step annealing strategy is used, directly placing the prepared absorber layer film on a 400°C hot stage under a nitrogen atmosphere for annealing for 10 minutes. Observation revealed that after one-step high-temperature annealing, a large area of the absorber layer film peeled off, making subsequent device fabrication impossible.
[0035] Example 4 This example uses conventional CdS as the electron transport layer, does not deposit a Se seed layer, and employs a conventional annealing strategy, mainly including the following: FTO conductive glass cleaning: Place the FTO glass on a cleaning rack and sequentially clean it with semiconductor cleaning solution, ultrapure water, and ultrasonic cleaning for 20 minutes each time. Then, place it in an oven to dry for later use. Before each use, treat the FTO conductive glass substrate with ultraviolet-ozone for 20 minutes to improve surface wettability.
[0036] Preparation of CdS electron transport layer: A CdS electron transport layer was deposited on a cleaned FTO glass substrate using a chemical bath. 10 mL of cadmium nitrate (Cd(NO3)2, 4.6 g / L), 13 mL of ammonia (NH3·H2O), and 6.4 mL of thiourea (CH4N2S, 114.2 g / L) were sequentially added to 70 mL of deionized water. After thorough stirring, the mixture was transferred to a glass bottle containing an FTO substrate and deposited in a chemical bath at 66 °C for 16 min 30 s. The substrate was then rinsed with deionized water and dried under nitrogen. Next, a 20 mg / mL CdCl2 methanol solution was spin-coated onto the FTO / CdS surface at 3000 rpm for 30 s, followed by annealing at 400 °C for 10 min in air.
[0037] Hydrothermal deposition of Sb2(S,Se)3 thin films: Potassium antimony tartrate (C8H4K2O) 12 Sb2·0.5H2O), sodium thiosulfate (Na2S2O3·5H2O), and selenourea (CH4N2Se) were dissolved in deionized water at a molar ratio of 4.5:18:1. After stirring evenly, the solution was transferred to a reaction vessel. The substrate with the Se seed layer deposited was placed in the reaction vessel at a 75° angle with the front side facing down. The reaction was carried out at 135°C for 2 h. After removal, the substrate was rinsed with deionized water and dried with nitrogen to obtain the deposited sample.
[0038] The deposited sample was annealed for 10 minutes on a 400°C hot stage under a nitrogen atmosphere.
[0039] A gold electrode with a thickness of 80 nm was deposited on the hole transport layer by thermal evaporation to obtain a complete solar cell device.
[0040] The performance of the solar cell device prepared in this embodiment was tested, and the measured open-circuit voltage was 0.657 V, short-circuit current density was 21.49 mA / cm2, fill factor was 61.67%, and photoelectric conversion efficiency was 8.71%.
[0041] Comparing the JV curves of solar cell devices prepared with optimized Se seed layer thickness in Examples 4 and 1, as shown... Figure 2 As shown, devices using TiO2 as the electron transport layer exhibit higher short-circuit current density compared to devices using CdS. This is because TiO2 has a wider bandgap, and its parasitic absorption in the short-wavelength region is significantly weaker than that of CdS, allowing more short-wavelength photons to reach the absorption layer and be effectively utilized.
[0042] Comparing the EQE curves of solar cell devices prepared with optimized Se seed layer thickness in Examples 4 and 1, as shown... Figure 3 As shown, the quantum efficiency of the solar cell device in Example 1 in the 300-550 nm short-wavelength region is significantly higher than that in Example 4, further confirming that the TiO2 electron transport layer can effectively reduce light loss in the short-wavelength region compared to CdS, thereby improving the overall photoelectric conversion efficiency of the device. Meanwhile, the quantum efficiency of Example 1 in the long-wavelength region is basically equivalent to that of Example 4, indicating that the Sb2(S,Se)3 absorber layer prepared by Se seed layer-assisted deposition combined with stepped annealing process has good crystal quality and carrier collection efficiency.
Claims
1. A TiO2 / Se composite buffer layer film, characterized in that, It includes a TiO2 electron transport layer coated on the surface of a substrate, and an ultrathin Se seed layer deposited on the surface of the TiO2 electron transport layer.
2. The method for preparing a TiO2 / Se composite buffer layer thin film as described in claim 1, characterized in that, Includes the following steps: Step 1: Coat an electron transport layer on the substrate surface, wherein the electron transport layer is TiO2; Step 2: Deposit an ultrathin Se seed layer on the surface of the electron transport layer to form a TiO2 / Se composite buffer layer film; The TiO 2 / Se composite buffer layer film is used to prepare Sb2(S,Se)3 absorber film by hydrothermal deposition.
3. The method for preparing a TiO2 / Se composite buffer layer thin film as described in claim 2, characterized in that, The thickness of the ultrathin Se seed layer is 3-7 nm.
4. The method for preparing a TiO2 / Se composite buffer layer thin film as described in claim 3, characterized in that, The ultrathin Se seed layer was deposited using a thermal evaporation method, with a vacuum degree of less than 4 × 10⁻⁴ during deposition. 4 Pa.
5. A method for preparing a deposition sample for preparing a solar cell, characterized in that, The TiO2 / Se composite buffer layer film obtained by the preparation method of any one of claims 2-4 further includes the following in step two: Step 3: Prepare a Sb2(S,Se)3 absorber film on the TiO2 / Se composite buffer layer film by hydrothermal deposition to obtain a deposited sample.
6. The method for preparing a deposition sample for preparing a solar cell as described in claim 5, characterized in that, The deposited sample in step three is subjected to step annealing: First, the sample is placed in nitrogen or inert gas and kept at 80-120℃ for 5-10 min. Then, the temperature is increased to 200℃ and 300℃ at a rate of 10℃ / min, and kept at each temperature for 5-10 min. Finally, the temperature is increased to 400℃ for annealing for 10 min. After natural cooling, the Sb2(S,Se)3 absorption layer is obtained.
7. The application of the TiO2 / Se composite buffer layer film as described in claim 1, or the TiO2 / Se composite buffer layer film prepared by the preparation method of any one of claims 2-4, or the deposited sample prepared by the preparation method of the deposited sample for preparing solar cells as described in any one of claims 5 and 6, in the preparation of solar cells.